2023
DOI: 10.1007/s42114-023-00804-3
|View full text |Cite
|
Sign up to set email alerts
|

Boron nitride whiskers and nano alumina synergistically enhancing the vertical thermal conductivity of epoxy-cellulose aerogel nanocomposites

Zhaoyang Li,
Duo Pan,
Ziyuan Han
et al.

Abstract: With the continuous innovation of electronic information technology, thermal interface materials, which mainly play the role of heat dissipation in microelectronic devices, will face great challenges. In this work, the boron nitride whiskers (BNWK)@Al 2 O 3 /cellulose aerogels (CA) obtained by electrostatic self-assembly one-dimensional BNWK and zero-dimensional nano-Al 2 O 3 combined with directional freezing of CA. The obtained BNWK@Al 2 O 3 /CA not only has a unique vertical network structure, but also exhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…A study demonstrated that the corrosion rate of glass ber/vinyl ester resin in 40 wt% H 2 SO 4 solution increased with immersion time and temperature [11]. Research indicated that the uorine-and boron-free glass bers can signi cantly enhance the acid resistance of composites [12]. A study identi ed that a particular high performance and general glass bers reinforced composites shows almost the same deterioration of mechanical properties under hot and humid conditions, while the high-performance ber reinforced composites showed a better corrosion resistance under acid and salt spray conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…A study demonstrated that the corrosion rate of glass ber/vinyl ester resin in 40 wt% H 2 SO 4 solution increased with immersion time and temperature [11]. Research indicated that the uorine-and boron-free glass bers can signi cantly enhance the acid resistance of composites [12]. A study identi ed that a particular high performance and general glass bers reinforced composites shows almost the same deterioration of mechanical properties under hot and humid conditions, while the high-performance ber reinforced composites showed a better corrosion resistance under acid and salt spray conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…For most phase change insulation materials, maintaining long-lasting insulation performance requires a large space volume due to fixed enthalpy values. Ceramic aerogel materials have low thermal conductivity and slow phonon transfer rate; especially for silica (SiO 2 ) aerogel, it has small pore size, high porosity and thermal stability, so it is a lightweight and efficient thermal insulation material [8,9]. However, in practical applications, researchers found that SiO 2 aerogel is highly transparent to infrared radiation and has great brittleness [10].…”
Section: Introductionmentioning
confidence: 99%